A New Laboratory Tool for COVID-19 Severity Prediction, CENIL Score - Elif Mukime Saricaoglu; Belgin Coskun; Muge Ayhan; Esragul Akinci; Bircan Kayaaslan; Adalet Aypak; Ayse Yasemin Tezer Tekce; Imran Hasanoglu; Ayse Kaya; Fatma Eser; Yesim Aybar Bilir; Burcu Ozdemir; et al. (Diagnostics)
Background/Objectives: Several studies investigated the risk factors for severe COVID-19-related outcomes. Early identification and proper treatment of COVID-19 patients who may develop severe pneumonia are crucial. The aim of this study was to detect the importance of the laboratory parameters for risk prediction of severe pneumonia in COVID-19 patients. Methods: This retrospective cohort study included COVID-19 patients’ laboratory parameters at admission. Biochemical, hematological, coagulation, and inflammatory parameters values were compared between the non-severe and severe groups. Results: A total of 534 COVID-19 patients were screened, and 472 of them were included in this study. The mean age of patients was 64 (±3.1) years; 242 (51.3%) were men. A total of 204 (43.2%) patients were diagnosed as severe cases. The independent predictors of severe illness were C-reactive peptide, Eosinophil, neutrophil–lymphocyte ratio, interleukin-6, and lactate dehydrogenase. These parameters were named as CENIL scores from 0 to 5 points. The findings of this study indicate that these biomarkers identified tend to increase progressively with disease severity in severe COVID-19 patients. Additionally, the CENIL risk score identified a specific cut-off value of 3, highlighting it as a critical threshold for identifying patients at high risk of severe COVID-19 progression. Conclusions: In this study, we identified biomarkers—including CRP, eosinophil count, NLR, IL-6, and LDH—named as CENIL risk score that can help predict the likelihood of severe disease at diagnosis. Clinicians may be more vigilant regarding the development of severe disease in patients with high CENIL risk scores, guided by clinical and radiological findings.